Characteristics and factors associated with initial antiretroviral medicine use among newly treated HIV/AIDS patients in Zhejiang Province, Eastern China: A cross-sectional study - Yue Chen; Wei Cheng; Jiezhe Yang; Jun Jiang; Lin Chen; Xiaohong Pan; Chengliang Chai; Jianmin Jiang (Preventive Medicine Reports)
Objective: This study investigated characteristics and factors associated with initial antiretroviral medicine use among newly treated HIV/AIDS patients in Zhejiang Province, China, from 2019 to 2023. Methods: Data from the National Free Antiretroviral Therapy (ART) Database, covering the period from 2019 to 2023, were analyzed. ART regimens were classified as nationally free or medicare/self-paid. A multivariable logistic regression analysis was employed to identify factors influencing the initial ART regimen choice among those newly treated HIV/AIDS patients. Results: In total, 17,018 individuals with HIV who initiated ART were included in the analysis. The use of medicare/self-paid medicines increased from 2.8 % to 39.8 %. Individuals with HIV transmission through homosexual contact (aOR = 1.30, 95 % CI: 1.16–1.45), those who received a diagnosis through medical institutions (aOR = 1.59, 95 % CI: 1.41–1.80), those with World Health Organization clinical stage IV disease (aOR = 1.93, 95 % CI: 1.62–2.29), and patients with the baseline CD4 cell count <50 cells/μL were more likely to opt for medicare/self-paid medications. Conclusion: The proportion of medicare/self-paid medicine use among newly treated HIV/AIDS patients exhibited an increasing trend. Several factors, including the education level, transmission route, diagnosis approach, and WHO clinical stage, among others, were associated with the medication choice. Taken together, our results provide crucial evidence to aid policymakers in developing procurement plans and allocating medicines appropriately to better address the diverse needs of HIV/AIDS patients.